Mycoflora and polyphenolics of variously coloured seeds of Bambara groundnut (Vigna subterranea L. Verdc.) - Aveling, Terry A.S. (University of Pretoria, 2013)
Dissertation (Magister Institutionis Agrariae)--University of Pretoria, 2005.